"Totally un-English"? : Britain's internment of "enemy aliens" in two world wars - Dove, Richard, 1938-2022 (Yearbook of the Research Centre for German and Austrian Exile Studies, 2005)
The internment of 'enemy aliens' by the British government in two world wars remains largely hidden from history. British historians have treated the subject - if at all - as a mere footnote to the main narrative of Britain at war. In the 'Great War', Britain interned some 30,000 German nationals, most of whom had been long-term residents. In fact, internment brought little discernible benefit, but cruelly damaged lives and livelihoods, breaking up families and disrupting social networks. In May 1940, under the threat of imminent invasion, the British government interned some 28,000 Germans an.